Sanctifying slavery and politics in South Carolina : the life of Reverend Alexander Garden, 1685-1756 - Witzig, Fred E. (Columbia, South Carolina : University of South Carolina Press, 2018)
"When Alexander Garden, a Scottish minister of the Church of England, arrived in South Carolina in 1720, he found a colony smoldering from the devastation of the Yamasee War and still suffering from economic upheaval, political factionalism, and rampant disease. It was also a colony turning enthusiastically toward plantation agriculture, made possible by African slave labor. In Sanctifying Slavery and Politics in South Carolina, the first published biography of Garden, Fred E. Witzig paints a vivid portrait of the religious leader and the South Carolina colony he helped shape"--
Birthplaces -- Acquaintances -- Friendship -- Dalliance -- Engagement -- Marriage -- Till death do us part.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Garden, Alexander, -- 1686-1756.; Church of England -- South Carolina -- Charleston -- Clergy -- Biography; Garden, Alexander, -- 1686-1756.; Church of England; South Carolina -- History -- Colonial period, ca. 1600-1775.; South Carolina -- Politics and government -- To 1775.; Slavery -- South Carolina -- History -- 18th century; Clergy; Politics and government; Slavery; South Carolina; South Carolina -- Charleston; BIOGRAPHY & AUTOBIOGRAPHY / Historical; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); To 1799; Biography; History; Electronic books